Pressure sensitive adhesive based on PFBA monomer for ePTFE bonding. Issue 23 (25th February 2022) - Li, Wei; Ma, Xiao‐Yan; Yan, Jie; Zou, Wei; Zheng, Wenjiang; Li, Yanli; Liang, Yanli
Abstract: Expanded polytetrafluoroethylene (ePTFE) has superior properties such as compression creep resistance and compression resilience, but it is difficult to bond with other materials due to its low surface energy, high crystallinity and highly symmetrical structure. In this paper, a new type of pressure‐sensitive adhesive is prepared from butyl acrylate, glycidyl methacrylate and unique pentafluorobenzyl acrylate, in which pentafluorophenyl group is introduced to provide steric hindrance to avoid clustering and increase the affinity with ePTFE simultaneously. The thermal stability of this pressure‐sensitive adhesive is approximately 250°C; the contact angle can reach 110.7°; the peel strength can reach 19 N/25 mm, comparable to literature values. The shear holding power at room temperature can be maintained over 100 h, and increases with the extension of immersion time in water, 5 times that of the literature report. This new adhesive can aptly solve the adhesion challenges with the use of ePTFE in complex environment. Abstract :